Multi-criteria analysis of economic activity for European Union member states and candidate countries: TOPSIS and WSA applications - (:unkn) unknown (My University, 2011)
This work presents the results obtained from an attempt for multi-criteria analysis of the economic activity in 2008 for European Union Member States and candidate countries. In analysis of the economic activities of member and candidate countries, five macroeconomic criteria have been considered. These are; Gross Domestic Product (GDP), Exports, Imports, Inflation rate and Unemployment rate. The European Union Member States and candidate countries were analyzed and sorted under the five criteria by means of TOPSIS and WSA methods.
Keywords: European union; Multi-criteria decision analysis; TOPSIS and WSA